2017
DOI: 10.1002/bmb.21046
|View full text |Cite
|
Sign up to set email alerts
|

Learning effectiveness and satisfaction of international medical students: Introducing a Hybrid–PBL curriculum in biochemistry

Abstract: A biochemistry course is a fundamental but important subject in medical education in China. In recent years, the number of international medical students has increased. Curriculum reform in biochemistry teaching is needed because of the knowledge limitations of students, a close linkage of biochemical content with clinics, the shortcomings of lecture-centered teaching, and the requirements for early clinical practice training and competence. In this study, we analyzed a novel curriculum reform, "Hybrid-PBL," w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 16 publications
0
27
0
3
Order By: Relevance
“…Yan et al used a questionnaire to evaluate students' perceptions of the Hybrid-PBL, which combines PBL with biochemistry lectures, and they found that the Hybrid-PBL curriculum was well accepted by the international students and could improve their understanding of biomedical concepts. 16 In a survey of medical students in Karachi, the students reported that PBL had helped them in developing their communication skills, their interpersonal relationships, and their problem-solving abilities. 17 In another study done at Shifa Medical College, Islamabad, 67% of the students reported a desire for a mix of both lectures and small-group learning (PBL).…”
Section: Discussionmentioning
confidence: 99%
“…Yan et al used a questionnaire to evaluate students' perceptions of the Hybrid-PBL, which combines PBL with biochemistry lectures, and they found that the Hybrid-PBL curriculum was well accepted by the international students and could improve their understanding of biomedical concepts. 16 In a survey of medical students in Karachi, the students reported that PBL had helped them in developing their communication skills, their interpersonal relationships, and their problem-solving abilities. 17 In another study done at Shifa Medical College, Islamabad, 67% of the students reported a desire for a mix of both lectures and small-group learning (PBL).…”
Section: Discussionmentioning
confidence: 99%
“…Yan et al 18 Os estudantes tiveram contato com a ABP em apenas um módulo, e a maioria concordou que o método proporcionou maior satisfação, visto que permitiu o desenvolvimento de algumas habilidades autodirecionadas, bem como a possibilidade de lidar melhor com o estresse.…”
Section: Trappler 17unclassified
“…We also find the influences of PBL on school curricula and curricular strength. Yan introduced PBL into an international biochemistry course, where it was widely accepted by the students, suggesting that it might be an important supplement to traditional pedagogy . A five‐year retrospective study found that the PBL curriculum at Saga Medical School greatly improved its overall strength .…”
Section: Pbl Outcomesmentioning
confidence: 99%